2023
DOI: 10.1007/s13311-023-01421-0
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Receptor Antagonist as Therapy for Traumatic Brain Injury

Caroline Lindblad,
Elham Rostami,
Adel Helmy

Abstract: Traumatic brain injury is a common type of acquired brain injury of varying severity carrying potentially deleterious consequences for the afflicted individuals, families, and society. Following the initial, traumatically induced insult, cellular injury processes ensue. These are believed to be amenable to treatment. Among such injuries, neuroinflammation has gained interest and has become a specific focus for both experimental and clinical researchers. Neuroinflammation is elicited almost immediately followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…Though IL-ra did not exhibit significant group differences in the LMMs, it was included in the model predicting CT+ status at admission and 2 weeks and was the only inflammation marker to show a positive association with intracranial findings. IL-ra is an endogenous receptor antagonist of IL-1ra [ 74 ] that is under investigation as a therapeutic target for TBI [ 75 , 76 ]. Its elevation in CT+ could therefore reflect endogenous repair mechanisms, although given it was only included in some CT models (but not MRI models), the clinical/biological relevance of this effect remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Though IL-ra did not exhibit significant group differences in the LMMs, it was included in the model predicting CT+ status at admission and 2 weeks and was the only inflammation marker to show a positive association with intracranial findings. IL-ra is an endogenous receptor antagonist of IL-1ra [ 74 ] that is under investigation as a therapeutic target for TBI [ 75 , 76 ]. Its elevation in CT+ could therefore reflect endogenous repair mechanisms, although given it was only included in some CT models (but not MRI models), the clinical/biological relevance of this effect remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal changes post-TBI reflect a disrupted endocrine system and may be predictive for patient outcomes including levels of plasma copeptin, nesfatin-1, and resistin [ 79 ]. A recent paper reported that IL-1 receptor antagonists as therapy for TBI [ 86 ]. Recent reports indicate that hyperbaric oxygen therapy (HBOT) was safe and beneficial in treating TBI including chronic sequelae of TBI [ 87 , 88 ].…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…After effective anti-inflammatory treatment, the expression levels of these cytokines were remarkably reduced, and cognitive dysfunction was effectively improved. [7][8][9][10][11][12][13] Of further note, IL-36 receptor antagonist (IL-36Rα) and IL-38, two anti-inflammatory cytokines with similar functions in IL-1F reduced neuronal death and improved cognitive function defects by down-regulating the expression levels of IL-1β, tumor necrosis factor α (TNFα), and IL-6. 14,15 Therefore, targeting inflammatory cytokines is a promising new therapy for the treatment of CNS diseases and injuries.…”
Section: Introductionmentioning
confidence: 99%